Meningkatan Prestasi Dan Motivasi Dalam Melakukan Senam Lantai Dengan Menggunakan Permainan - yulidar yulidar (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Floor Gymnastics is one of the sub-subjects in the study of Physical Education of Health Sports (Penjasorkes), in conducting floor gymnastics required various mental and good skills. The problem formulation is: